ANALISIS RISIKO TERHADAP WAKTU PELAKSANAAN PEMBANGUNAN PERUMAHAN DI KOTA DENPASAR - Ida Bagus Gde Manuaba (Universitas Dwijendra, 2014)
Implementation of housing projects in the city of Denpasar are common thingsÂ that are not in accordance with the plan, which is one of them is the uncertainty of timing issues in the field of project implementation. lack of risk uncertainty at this stage of project implementation time depends on the coordination and control of all stakeholders including the project owner that takes skill, knowledge and experience for the party - related party. Therefore, to control the factors causing uncertainty in identifying the need and the comprehensive risk analysis, so the possibility of bad risks arising darai be pressed / in minimalism.Research methods in identifying the risks is a way of brainstorming and interviews as well as distributing questionnaires to the parties - the profession of housing associations, contractors and project owners after the conducted an assessment of the risks - risks identified a risk that the dominant (major risk), the risk category is unacceptable (Unacceptable) and the risk of unexpected (Undesirable), further mitigation measures / handling to minimize the harmful effects of these risk .The results obtained risks - risks identified are as many as 51 (fifty one) risks involved in the implementation of housing projects. After an assessment at the level of acceptance of risk (risk acceptability) generate risk the category is not acceptable (unacceptable) there are 2 (two) risk (3.92%), and the risk of unintended (undesirable) there are 49 (forty nine) risk (96.08%). the category of acceptable (acceptable) and there is no risk in Gori said negligible (negligible) also there is no risk. Data processing is performed statistical diskriptip assisted by using SPSS software version 17 and Microsoft Excel.Comparison of risk that is not expected (Undesirable) consists of 4 (four) risk (8.16%) sourced from the political risk, one (1) risk (2.04%) of the environmental risk, 3 (three) risk (6.12%) of risk perncanaan, 1 (one) risk (2.04) of marketing ridiko, 3 (three) risk (6.12%) of economic risk, 1 (one) risk (2.04) of financial ridiko, 3 (three) risk (6.12%) of the natural risk, 12 (twelve) risk (24.49%) of project risk, 2 (two) risk (4.08%) of the technical risk, 16 (sixteen) risk (32.65) of human risk, 1 (one) risk (2.04) of criminal risk, 2 (two) risk (4.08%) of the safety risk. The most dominant (major risk) rooted in human risk is: execution of work due to the disruption of traditional ceremonies, defects arising from design changes, the amount of wasted materials, methods of implementation proposed by the contractor is less precise, method of taking a job working in a less supportive, organization's internal strife contractor, owner familiar with the different contractors, different culture / cultural influences between the labor and material changes from the owner. Keywords: time risk, risk identification, assessment, mitigation.